2020
DOI: 10.3390/cells9051112
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Restrictions: A New Concept Governing HIV-1 Spread Emerging from Integrated Experimental-Computational Analysis of Tissue-Like 3D Cultures

Abstract: HIV-1 can use cell-free and cell-associated transmission modes to infect new target cells, but how the virus spreads in the infected host remains to be determined. We recently established 3D collagen cultures to study HIV-1 spread in tissue-like environments and applied iterative cycles of experimentation and computation to develop a first in silico model to describe the dynamics of HIV-1 spread in complex tissue. These analyses (i) revealed that 3D collagen environments restrict cell-free HIV-1 infection but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 101 publications
2
8
0
Order By: Relevance
“…The consistent differences in the results observed when the different serum lots were utilized suggest that the contribution of each transmission mode may be influenced by the environmental conditions encountered. The observation that viral transmission modes were influenced by environmental conditions is in line with observations made for other viruses, such as HIV-1 [ 26 , 32 ], and highlights the utility of trying to incorporating more physiologically relevant conditions and altering other aspects of cell culture environments (e.g., concentrations of lipids, iron, and other components of serum) in future experiments when studying viral spread [ 33 ], as well as accounting for these factors within the mathematical models used to analyze these data.…”
Section: Discussionsupporting
confidence: 86%
“…The consistent differences in the results observed when the different serum lots were utilized suggest that the contribution of each transmission mode may be influenced by the environmental conditions encountered. The observation that viral transmission modes were influenced by environmental conditions is in line with observations made for other viruses, such as HIV-1 [ 26 , 32 ], and highlights the utility of trying to incorporating more physiologically relevant conditions and altering other aspects of cell culture environments (e.g., concentrations of lipids, iron, and other components of serum) in future experiments when studying viral spread [ 33 ], as well as accounting for these factors within the mathematical models used to analyze these data.…”
Section: Discussionsupporting
confidence: 86%
“…These results suggest that the contribution of each transmission mode may be influenced by the environmental conditions encountered. The observation that viral transmission modes are influenced by environmental conditions is in line with observations made for other viruses, such as HIV-1 [20,21] and highlights the utility of trying to incorporating more physiologically relevant conditions in future experiments when studying viral spread [22]. Arguably, cell proliferation dynamics could have an impact on the efficacy of viral transmission modes.…”
Section: Discussionsupporting
confidence: 75%
“…The inoculum was then removed, and the wells were rinsed twice with warm cDMEM before adding 200µL fresh cDMEM with 10% FBS. Media and cell lysates were collected from triplicate wells at 0, 3,6,9,12,15,18,21,24,27,30,36,42,48, 72 and hours post inoculation (p.i.). To determine the amount of cell division, cells in parallel wells were counted at 0, 36, 72 and 96 hours post-inoculation.…”
Section: High Moi Hcv Life Cycle Kineticsmentioning
confidence: 99%
“…We first tested whether PMNs release NETs in this experimental system, as described to occur in response to high amounts of HIV 1 viral particles and to reduce HIV infectivity. 36 We therefore considered the possibility that HIV-1 particles released in the cell culture supernatant or the local high concentrations of HIV-1 particles at cell-cell contacts formed to transmit the virus from infected donor to uninfected target cells (virological synapse) 40 , 53 , 54 , 55 might trigger a similar response and contribute to the anti-HIV-1 activity in HLACs. Hence, we incubated PMNs with various amounts of HIV particles (between 1 × 10 7 –5 × 10 8 pU RT/μL) and stained these samples for DNA and MPO to detect NETs ( Figures 5 B and S5 A).…”
Section: Resultsmentioning
confidence: 99%
“… 36 , 37 , 38 Although these studies indicated that PMNs may be able to exert anti-HIV activity, they did not assess whether PMNs impair HIV-1 replication in physiologically relevant target cells and tissue, where virus spread occurs predominately via cell-associated transmission and not cell-free virus particles. 39 , 40 , 41 We therefore set out to study the effects of PMNs on HIV-1 replication in ex vivo cultures of human tonsil tissue and peripheral blood mononuclear cells (PBMCs). We find that PMNs exert immediate and potent anti-HIV-1 activity that requires direct cell-cell contact but is not mediated by any of the classic PMN effector functions described so far.…”
Section: Introductionmentioning
confidence: 99%